The risk of offspring mood and anxiety disorders in the context of prenatal maternal somatic diseases: a systematic review and meta-analysis. (12th January 2022) - Gong, Xiayu; Fan, Zhixin; Xu, Hanfang; Wang, Hanzhang; Zeng, Ningxi; Li, Ling; Wu, Lili; Yan, Can
Abstract: Aims: The importance of prenatal maternal somatic diseases for offspring mood and anxiety disorders may be overlooked or undervalued. We conducted the first systematic review and meta-analysis assessing the risk of offspring mood and anxiety disorders in the context of prenatal maternal somatic diseases. Methods: We screened articles indexed in Embase (including Embase, MEDLINE, PubMed-not-MEDLINE), PsycARTICLES and PsycINFO databases up to August 2021. 21 studies were included. We examined the overall associations between prenatal maternal somatic diseases and offspring mood/anxiety disorders. Analyses were stratified according to maternal somatic diseases and follow-up duration. Results: We observed an increased risk of mood and anxiety disorders in the context of prenatal maternal somatic diseases [relative risk (RR) = 1.26; 95% confidence interval (CI) 1.15–1.37, RR = 1.31; 95% CI 1.24–1.38]; maternal obesity(RR = 1.92; 95% CI 1.72–2.11), hypertensive disorders (RR = 1.49; 95% CI 1.11–1.86) and infertility (RR = 1.26, 95% CI 1.14–1.39) were risk factors for mood disorders; maternal polycystic ovary syndrome (RR = 1.61; 95% CI 1.42–1.80), severe obesity (RR = 1.56; 95% CI 1.44–1.68) and moderate obesity (RR = 1.36; 95% CI 1.28–1.44) were risk factors for anxiety disorders. Prenatal maternal somatic diseases increased the risk of mood disorders in childhood and adulthood (RR = 1.71; 95% CI 1.34–2.09/RR = 1.19; 95% CI 1.09–1.30), as well as the risk of anxiety disorders in adulthood (RR = 1.33; 95% CI 1.26–1.41). Conclusion: The results indicate that prenatal maternal somatic diseases are associated with offspring mood and anxiety disorders, and that the associations may be long-lasting.